INFLUENCES OF PHYSALIS PERUVIANA L. AND LUPINUS ALBUS L. EXTRACTS ON THE LEVELS OF SOME BIOCHEMICAL PARAMETERS IN ERYTHROCYTES AND SERUM OF STREPTOZOTOCIN INDUCED DIABETIC RATS - Erman, Fazilet; Kaya, Tubay; Yilmaz, Okkes; Erman, Orhan; Ozsahin, Ayse Dilek (Parlar Scientific Publications (P S P), 2017)
In this study, the effects of goldenberry and lupin on some biochemical parameters in erythrocytes and serum of streptozotocin-induced diabetic rats were investigated. Type II diabetes was produced in rats by the streptozotocin injection. Rats were divided into four groups, each one containing 10 rats: non-diabetic control group, STZ-Diabetes type II group, STZ-Diabetes type II+goldenberry group, and STZ-Diabetes type II+lupin group. After one week from the injection, goldenberry and lupin were administered to rats for 2 months. Malondialdehyde, glutathione and fatty acid levels, which are signs of lipid peroxidation, were measured in erythrocytes and serum. At the beginning and end of the study, postprandial blood glucose levels of the rats were measured. In type II diabetes, malondialdehyde level was increased when compared to control group. Glutathione level was decreased in the erythrocytes and all of the STZ-induced diabetic groups. It has been determined that the treatment with similar doses of goldenberry and lupin significantly reduced postprandial hyperglycemia, oxidative stress and augmented antioxidant system. The results of the present study showed that the plant extracts exerted anti-hyperglycemic effects and consequently may alleviative tissue damage caused by streptozotocininduced diabetes.
Keywords: Diabetes; Erythrocytes; Goldenberry; Lipid peroxidation; Lupin; Serum